Dietary Piperine is Transferred into the Milk of Nursing Mothers - N´Diaye, Katharina; Debong, Marcel; Behr, Jürgen; Dirndorfer, Sebastian; Duggan, Tara; Beusch, Anja; Schlagbauer, Verena; Dawid, Corinna; Loos, Helene; Büttner, Andrea; Lang, Roman; Hofmann, Thomas (Molecular Nutrition & Food Research, 2021)
Introduction: The diet of breastfeeding mothers could bring nurslings into contact with flavor compounds putatively contributing to early sensory programming of the infant. The study investigates whether tastants from a customary curry dish consumed by mothers are detectable in their milk afterwards and can be perceived by the infant. Methods and Results: Sensory evaluation identifies pungency as the dominating taste impression of the curry dish. Its ingredients of chili, pepper, and ginger suggest the flavor compounds capsaicin, piperine, and 6-gingerol as analytical targets. Breastfeeding mothers are recruited for an intervention trial involving the consumption of the curry dish and subsequent collection of milk samples for flavor compound analysis. Targeted and untargeted mass spectrometric (MS)- investigations identify exclusively piperine as an intervention-derived compound in human milk. However, concentrations are below the human taste threshold. Conclusion: Piperine from pepper-containing foods transfers into the mother's milk within 1 h and is delivered to the nursling. Concentrations of 50 and 200 nM of piperine are 70–350 times below the human taste threshold, but TRPV1 (Transient Receptor Potential Vanilloid-1 ion channel) desensitization through frequent exposure to sub-taste-threshold concentrations could contribute to an increased tolerance at a later age.
CRIS-Team Scopus Importer:2021-10-29
Keywords: human milk; metabonomics; piperine; sensory programming